2019
DOI: 10.1186/s13634-019-0644-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transient modeling for appliance characterization

Abstract: Transient signals are characteristic of the underlying phenomenon generating them, which makes their analysis useful in many fields. Transients occur as a sudden change between two steady state regimes, subsist for a short period, and tend to decay over time. Hence, superimposed damped sinusoids (SDS) were extensively used for transients modeling as they are adequate for describing decaying phenomena. However, SDS are not adapted for modeling the turn-on transient current of electrical appliances as it tends t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Changes in power or current are associated with signal analysis in time-domain, in which the event detection is based, for instance, on the apparent power to determine the instant of an event, as presented in the Half-Cycle Apparent Power (HCApP) method, proposed in [9]. A similar approach, using the envelope of electrical current and an adaptive threshold-based method, is presented in [10,11], defined as High-Accuracy NILM Detector (HAND). Furthermore, considering the need to detect signatures based on state change characteristics, in [12], an event detection is presented for multiple state loads, using the concept of powerlets [13], which were defined as groups of short sequences that characterize an appliance.…”
Section: Review Of Techniques For Load Event Detection and Power Signature Recognitionmentioning
confidence: 99%
See 4 more Smart Citations
“…Changes in power or current are associated with signal analysis in time-domain, in which the event detection is based, for instance, on the apparent power to determine the instant of an event, as presented in the Half-Cycle Apparent Power (HCApP) method, proposed in [9]. A similar approach, using the envelope of electrical current and an adaptive threshold-based method, is presented in [10,11], defined as High-Accuracy NILM Detector (HAND). Furthermore, considering the need to detect signatures based on state change characteristics, in [12], an event detection is presented for multiple state loads, using the concept of powerlets [13], which were defined as groups of short sequences that characterize an appliance.…”
Section: Review Of Techniques For Load Event Detection and Power Signature Recognitionmentioning
confidence: 99%
“…In [10], a modification of the Fourier Transform, incorporating an exponential damping, is proposed. The authors demonstrate that the identification of the damping observed during the transients improves the classification performance when combined with Fourier coefficients, achieving an accuracy of 90-99% for the COOLL dataset, even for unsupervised approaches.…”
Section: Review Of Techniques For Load Event Detection and Power Signature Recognitionmentioning
confidence: 99%
See 3 more Smart Citations